Innovations in the Federal Police investigation: the judicial police activity management system - Bandolin, Paulo César; Barros, Camila Monteiro de; Cândido, Ana Clara (Advanced Notes in Information Science, 2023)
This work seeks to analyze the innovation action implemented by the Federal Police with the development of the software solution called the Judiciary Police Activity Management System (ePol), whose primary functions are the materialization and management of all Federal Police Inquiries. This new system replaced the old Siscart, which had local databases in each Federal Police Unit and limited resources. The analysis of ePol as an innovation activity in the public sector was carried out from a literature review aiming to clarify the main concepts of innovation, mainly those present in the Oslo Manual, and the specificities of Innovation in the Public Sector. Notes were made on aspects of innovation particular to the case of the implementation of ePol, by specifying the main characteristics of this tool as Innovation.